Penggunaan New Media dalam Promosi Pariwisata Daerah Situs Cagar Budaya di Indonesia - Ida Ri'aeni (Program Studi Ilmu Komunikasi, 2015)
Using new media, the limitations of space and time will no longer be an obstacle in introducing tourism place and attracting tourists to visit The use of new media can also make regional tourism in Indonesia grew more rapidly. The tourism sector is one of the expected development of the sector can be a major source of foreign exchange, expand, and create the entrepreneur opportunity as well as employment. Almost all countries in the world are trying to develop the tourism industry. The tourism industry has a bright prospect and is considered quite promising and brings many profits. The country has been managing the tourism sectors intensively and professionally to be foreign exchange revenue of the industry that accounts for a large number of countries.This research uses descriptive qualitative approach. The use of new media such as twitter, facebook, and internet sites can be utilized by Governments and private parties to be able to introduce objects and attractions that exist in the area. The focus in the research is: (1) what are the new media of promotion of cultural heritage in tourism areas in Cirebon? (2) How is the effectiveness of the use of new media in such promotional activities?In Cirebon, the development of the tourism potential of the region is able to give a positive impact with the presence of a great change in the life of the community. Economically, tourism is impacted in the expansion of the field of business and job opportunities, increase annual income and devisa in foreign countries. In the field of social life, social interaction occurs between the cultures of immigrants and the local population. It cause a change in the way of life of society as well as the occurrence of social integration. Next in anthropological concepts, knowledge of the culture and values of local wisdom are more sustainable and widely known.